2001
DOI: 10.1159/000047617
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation in Stroke Research

Abstract: Background and Purpose: Before developing new medical facilities or adapting existing facilities in the field of stroke, it is desirable to assess not only the medical, but also the economic consequences of such facilities. Economic evaluation studies differ from other outcome studies in the way that costs are compared with effects. The purpose of this paper is to give an insight into economic evaluation studies in the field of stroke, so that these studies become easier for neurologists to understand and to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
2
10
0
1
Order By: Relevance
“…Our results support the findings of existing reviews 4,[33][34][35][36][37][38][39] in that cerebrovascular diseases pose a significant economic burden. However, previous reviews have tended to focus on specific types of costing studies such as those used as part of an economic evaluation.…”
Section: Luengo-fernandez Et Al Cerebrovascular Disease Costs E21supporting
confidence: 91%
“…Our results support the findings of existing reviews 4,[33][34][35][36][37][38][39] in that cerebrovascular diseases pose a significant economic burden. However, previous reviews have tended to focus on specific types of costing studies such as those used as part of an economic evaluation.…”
Section: Luengo-fernandez Et Al Cerebrovascular Disease Costs E21supporting
confidence: 91%
“…excluding social care and indirect costs) in Europe and the USA. 15 The cost of stroke in the UK is high at £2300 million per year, and accounts for about 6% of total NHS and Social Services expenditure; this is nearly twice the amount spent on coronary heart disease (CHD). 2,16 Despite this high disease burden on society and high cost, little is known about the key aspects of managing stroke and how they affect the outcome and the cost.…”
Section: The Cost Of Strokementioning
confidence: 99%
“…One study (15 neuroimaging twice within the first 24 hours, the first scan negative and the second scan positive for haemorrhage. 117 They suggested that early haemorrhagic transformation may present as primary intracerebral haemorrhage if patients are not scanned very early.…”
Section: Studies Of Ct and Haemorrhagic Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…R educing the cost of health care has become increasingly important in the advent of rising costs, 1 and the treatment of stroke is no exception. 2 The high morbidity associated with stroke contributes to the economic burden of this condition worldwide, [3][4][5] with hospital costs accounting for 71% of the total stroke care costs.…”
mentioning
confidence: 99%